Biocontrol Potential, Genome and Nonribosomal Peptide Synthetase Gene Expression of Bacillus velezensis 2211 - Nantawan Niemhom; Chokchai Kittiwongwattana (Current Applied Science and Technology, 2022)
Members of the genus Bacillus produced a diverse group of antimicrobial compounds. Here, we presented the antifungal activity and genome sequence analysis of Bacillus sp. 2211, a potential plant-growth-promoting bacterium. Bacterial supernatants from strain 2211 cultures in nutrient broth (NB) and potato dextrose broth (PDB) suppressed the mycelial growth of Pyricularia oryzae, Colletotrichum aenigma, Colletotrichum fructicola and Fusarium oxysporum. The supernatants were also able to suppress spore germination of these fungi, except for F. oxysporum. However, the supernatant from PDB displayed a significantly higher inhibition activity than NB. Additionally, the supernatant from PDB significantly reduced the disease severity caused by P. oryzae on rice seedlings. The genome of strain 2211 was sequenced. The highest digital DNA-DNA hybridization (80.1%) and average nucleotide identity (97.57%) levels indicated that strain 2211 was a member of the species Bacillus velezensis. The phylogenomic analysis showed that it clustered with B. velezensis NRRL B-41580T, B. velezensis KACC 13105 and B. velezensis subsp. plantarum FZB42T. The gene expression analysis showed the up-regulation of nonribosomal peptide synthetase (NRPS) genes bmyA, fenB and dhbE in PDB, compared to NB. This work demonstrated that the culture media affected the antagonistic activity of strain 2211 possibly through the modification of NRPS biosynthesis genes.
Keywords: Plant-Microbe Interactions and Immunity; Probiotics and Fermented Foods; Antimicrobial Peptides and Activities